ТАРЖИМА МУАММОЛАРИ (Махтумқули ижодининг ўзбекча таржималари мисолида) - Сапаева, Ф.Д. (SCIENCE and SOCIETY, 2017)
The article is about the interpreters of the poems by Mahtumkuli in to the Uzbek language. In the article the translators` skill in using words in the process of translating the poems by Makhtumquli has been analyzed, the value of word in literary- artistic translation is also discussed.
Keywords: Mahtumkuli; poem; translation; the Turkmen language; the Uzbek language; content; meaning; translator